Śp. Bp Dr Stanisław Józef Stefanek (1936-2020) - Krupka, Jan (Biuletyn Stowarzyszenia Kanonistów Polskich, 2020)
Bp Stanisław Józef Stefanek urodził się 7 maja 1936 r. w Majdanie Sobieszczańskim, w rodzinie rolniczej.